2020
DOI: 10.1002/sim.8703
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian time‐to‐event pharmacokinetic model for phase I dose‐escalation trials with multiple schedules

Abstract: Phase I dose‐escalation trials must be guided by a safety model in order to avoid exposing patients to unacceptably high risk of toxicities. Traditionally, these trials are based on one type of schedule. In more recent practice, however, there is often a need to consider more than one schedule, which means that in addition to the dose itself, the schedule needs to be varied in the trial. Hence, the aim is finding an acceptable dose‐schedule combination. However, most established methods for dose‐escalation tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…We accounted for all types of DLT while allowing the explicit modeling of the main type of toxicity expected (CRS) with PK/PD. Some dose‐finding methods have been proposed that include PK measures 26,52 . However, as PK/PD measures are analyzed by batch (and therefore are not available in real time) and the PK/PD models are developed after several cohorts of patients, a full sequential dose‐allocation approach can be difficult to perform in practice.…”
Section: Discussionmentioning
confidence: 99%
“…We accounted for all types of DLT while allowing the explicit modeling of the main type of toxicity expected (CRS) with PK/PD. Some dose‐finding methods have been proposed that include PK measures 26,52 . However, as PK/PD measures are analyzed by batch (and therefore are not available in real time) and the PK/PD models are developed after several cohorts of patients, a full sequential dose‐allocation approach can be difficult to perform in practice.…”
Section: Discussionmentioning
confidence: 99%
“…TITE-PK for sequential phase I trials TITE-PK for simultaneous investigation of multiple schedules in phase I trials were introduced in Günhan et al [7], here we adapt it for sequential investigation of multiple schedules. The time-to-first DLT events are modeled using a time-varying (non-homogeneous) Poisson process.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Günhan et al [7] proposed an alternative dose-schedule finding method, a Bayesian time-to-event pharmacokinetics model (TITE-PK), which uses pharmacokinetics (PK) principles. Unlike other phase I methods, TITE-PK makes use of an exposure-response model that is often more informative than a standard doseresponse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent simulation study showed how integrating PK information into the dose escalation design could enrich the knowledge of the dose-toxicity relationship, thus facilitating better dose recommendations for subsequent trials [37]. Recently, new designs that incorporate PK measurements into the dose escalation process [38] or PK/PD in the final dose-response curve estimation [39] have been proposed. Therefore, in order to maximize the probability of clinical success of alternative therapies such as immunomodulation, all available knowledge regarding PK, PD, and toxicology should be modelled and applied as early in the drug research and development process as possible.…”
Section: Introductionmentioning
confidence: 99%